Integrating Green Economy Principles into Islamic Economic Policy: A Systematic Review of Evidence from Indonesia (2015–2025): Mengintegrasikan Prinsip Ekonomi Hijau ke dalam Kebijakan Ekonomi Islam: Suatu Tinjauan Sistematis atas Bukti dari Indonesia (2015–2025) - Lucky y Al Hafz; Fandri Anani (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2025)
This study conducts a systematic literature review of 142 Scopus-indexed publications (2015–2025) to examine the integration of green economy principles into Islamic economic development policies in Indonesia. The objective is to map conceptual and empirical evidence, identify thematic patterns, and highlight policy implications. Following PRISMA 2020 guidelines, the review employed structured search strings, inclusion–exclusion criteria, and thematic synthesis. The findings reveal that green sukuk has emerged as a key instrument for financing renewable energy, low-emission transportation, and waste management projects, while regulators such as the Ministry of Finance, OJK, and Bank Indonesia have introduced roadmaps, green taxonomies, and impact reporting mechanisms. Conceptually, the literature underscores the alignment of maqāṣid al-sharīʿah with sustainable development goals, yet implementation gaps remain due to inconsistent metrics, limited impact assurance, and insufficient causal evaluations. The synthesis highlights five core themes: Islamic green finance instruments, regulatory frameworks, maqāṣid–SDGs alignment, real-sector implementation, and institutional barriers. This review contributes to the body of knowledge by offering the first comprehensive synthesis of Islamic green economy integration in Indonesia, emphasizing the need for future research on causal effectiveness, standardized indicators, and the inclusion of SMEs in sustainable finance. The study concludes that a hybrid model combining Islamic values, public policy, and global sustainability standards can serve as a blueprint for other Muslim-majority economies.